From status to emotion: What drives Apple brand love and willingness to pay? - Wibisono, Rafidianto; Nofrizal, Nofrizal; Zaki, Hammam; N, Arizal (Jurnal Siasat Bisnis, 2026)
Purpose – This study addresses the limited empirical evidence regarding how psychological and social factors influence brand love and willingness to pay (WTP) for premium technology brands such as Apple. Previous studies have primarily focused on functional and quality-based determinants of consumer loyalty, while the roles of social status, Fear of Missing Out (FoMO), and hedonism in shaping emotional attachment and willingness to pay remain insufficiently explored. Therefore, this study investigates how these factors collectively influence consumers’ brand love and willingness to pay for Apple products.Design/methodology/approach – A quantitative survey approach was employed to collect data from 654 Apple consumers. The data were subsequently analyzed using Structural Equation Modeling (SEM) with SmartPLS software.Finding – The findings indicate that social status, FoMO, and hedonism significantly influence consumers’ brand love and willingness to pay for Apple products. However, social status did not have a significant effect on brand love, while FoMO did not directly influence willingness to pay. In addition, brand love and hedonism played important mediating roles in explaining consumers’ premium purchasing behavior.Research limitation/implications – This study employed a quantitative survey of Apple users in Indonesia; therefore, the findings cannot be generalized to other cultural or market contexts, nor can causal relationships be established. In addition, the study focused only on social status, FoMO, and hedonism without considering other potential factors or changes in consumer behavior over time.Practical implication – Apple should strengthen its exclusive brand image through limited edition offerings, premium collaborations, partnerships with luxury influencers, and personalized consumer experiences to enhance customer loyalty and perceived value.Originality/value – The novelty of this study lies in its examination of psychological factors namely social status, FoMO, and hedonism as determinants of brand love and willingness to pay for the Apple brand, with hedonism acting as a rarely explored mediating variable.